Determinants of Sailors' Protective Behaviors in Fishing Spots against the Risks of Sunlight and Skin Cancer: A Qualitative Study in Iran. (17th July 2021) - Asadian, Ali; Fattahi Ardakani, Mojtaba; Sotoudeh, Ahmad; Zareipour, Moradali; Movahed, Ehsan
Abstract : Introduction . The growing rate of nonmelanoma skin cancer (NMSC) and melanoma has been a great challenge for global health system. The present research aims to determine sailors' protective behaviors against the risks of sunlight and skin cancer in Iran. Materials and Methods . The present research was qualitative in type, and its data were collected from August to December 2019. To this aim, 23 participants were recruited with whom semistructured interviews were held. The data collection continued until data saturation, and the interviews were coded in MAXQDA 10. Conventional content analysis was used to analyze the qualitative data. Results . Analysis of sailors' perceptions and experiences revealed 7 categories: protective behaviors, hard personal and familial conditions, social interactions, poor social support, feeling of satisfaction, self-care, and fear. Conclusion . Sailors are prone to skin cancer due to their specific work conditions. Perceptions and determinants of skin cancer and protective behaviors against sunlight were identified among sailors. Promotion of protective behaviors and beliefs that impeded preventive behaviors are among issues that require special attention.